Entre direitos e deveres: um estudo sobre as literaturas africanas e afro-brasileiras nos cursos de letras para o atendimento ?? lei 10.639/2003 - Oliveira, Cl??udia Cristina de (2016)
The law n?? 10.639/2003 promoted undeniable achievements, which provide new debates in education area around the possibilities that the knowledge and dissemination of African and Afro-Brazilian cultures can offer to expand the debate on multiculturalism. It promotes dialogue on the subject of blackness, since African ethnicity underlies the formation of the Brazilian people. For this debate be established as standardized educational practice, however, it is necessary to the critical examination of teacher education, questioning the common places until then in vogue in education, perpetuating prejudices. Thus, this research aims to analysis and reflection on the effects regarding the law 10.639/2003 and the consequences on teacher formation at graduation level in the course of Portuguese and Literatures - one of the areas of knowledge that the law mentions directly -, based on the questioning of formation of higher education in Brazil and the structural inequalities of education, particularly the insertion of black and African descent within our society. Investigates and discusses the formation of the literature professor, the subject reader trainer, so that the discussion of aspects of the afro-brazilian literature and the literature of Portuguese-speaking African countries can contribute as sources for reflection on the identity of the Brazilian people, the black and African descent in their individual and collective training, questioning coloniality of minds and the benefits of literary literacy